THE EFFECT OF HOTEL TAX, NUMBER OF HOTEL, AND NUMBER OF HOTEL GUEST ON LOCAL TAX REVENUE (STUDY CASE IN BATU PERIOD 2007-2010) - Ekki Giswagama Ibrahim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This study aims to determine the effect of hotel tax, number of hotel and number of hotel guest on local revenue. The Data used in this research is time series that the period 2007-2016 sourced from Central Bureau of Statistics. This study using multiple linear regression analysis method. The result of this study indicate that there is influence on hotel tax, number of hotel an number of hotel guest on local tax revenue, this is indicated by the regression of Adjusted Square of 94% and the rest of 6% influenced by other factors. In this research, just hotel tax has significance effect to the local tax revenue. Keyword : Local Tax, Hotel, Hotel Tax